2024
DOI: 10.5194/acp-24-3785-2024
|View full text |Cite
|
Sign up to set email alerts
|

Measurement report: Insights into the chemical composition and origin of molecular clusters and potential precursor molecules present in the free troposphere over the southern Indian Ocean: observations from the Maïdo Observatory (2150 m a.s.l., Réunion)

Romain Salignat,
Matti Rissanen,
Siddharth Iyer
et al.

Abstract: Abstract. New particle formation (NPF) in the free troposphere (FT) is thought to be a significant source of particles over the oceans. The entrainment of particles initially formed in the marine FT is further suspected to be a major contributor to cloud condensation nuclei (CCN) number concentrations in the marine boundary layer (BL). Yet, little is known about the process and, more broadly, about the composition of the marine FT, which remains poorly explored due to access difficulties. Here we report measur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 102 publications
0
1
0
Order By: Relevance
“…The simulated and modeled gas-phase concentrations at both Aboa and Neumayer are shown in Figure 3 44 However, the simulated trend of an increase in [IA] during daytime has earlier been observed in field campaigns conducted at the Mai ̈do observatory in the Reunion Island, 23,45 SMEAR I, 46 Michelstadt-Vielbrunn/Odenwald in Germany, 47 at the Marambio station on the Antarctic peninsula, 13 and in polluted urban cities of China (Beijing and Nanjing). 48 Recent CLOUD chamber studies have shown that in typical Antarctic and SO environments where the median IA/H 2 SO 4 ratios are 0.1 or higher, IA can increase particle formation rates by a factor of ∼10 or more compared to the H 2 SO 4 −NH 3 pathway.…”
Section: Particle Formation At Aboa and Neumayermentioning
confidence: 79%
“…The simulated and modeled gas-phase concentrations at both Aboa and Neumayer are shown in Figure 3 44 However, the simulated trend of an increase in [IA] during daytime has earlier been observed in field campaigns conducted at the Mai ̈do observatory in the Reunion Island, 23,45 SMEAR I, 46 Michelstadt-Vielbrunn/Odenwald in Germany, 47 at the Marambio station on the Antarctic peninsula, 13 and in polluted urban cities of China (Beijing and Nanjing). 48 Recent CLOUD chamber studies have shown that in typical Antarctic and SO environments where the median IA/H 2 SO 4 ratios are 0.1 or higher, IA can increase particle formation rates by a factor of ∼10 or more compared to the H 2 SO 4 −NH 3 pathway.…”
Section: Particle Formation At Aboa and Neumayermentioning
confidence: 79%